2018
DOI: 10.3390/en12010055
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Monitoring Based on Higher-Order Statistics: A Scalable Proposal for the Smart Grid

Abstract: The increasing development of the smart grid demands reliable monitoring of the power quality at different levels, introducing more and more measurement points. In this framework, the advanced metering infrastructure must deal with this large amount of data, storage capabilities, improving visualization, and introducing customer-oriented interfaces. This work proposes a method that optimizes the smart grid data, monitoring the real voltage supplied based on higher order statistics. The method proposes monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In [18], the index is primarily tested during a short-term one-week campaign, which is an effective tool for voltage characterization using HOS. Two strategies are extracted: the first strategy detects the extreme values of the PQ events; and the second one consists of the continuous monitoring patterns of working and non-working days.…”
Section: A Pq Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…In [18], the index is primarily tested during a short-term one-week campaign, which is an effective tool for voltage characterization using HOS. Two strategies are extracted: the first strategy detects the extreme values of the PQ events; and the second one consists of the continuous monitoring patterns of working and non-working days.…”
Section: A Pq Indexmentioning
confidence: 99%
“…This contributes to improving future prediction tools based on artificial intelligence. The authors' previous work [18] settled down the basis of the index and showed a preliminary controlled experience that has been tested and validated in the current work.…”
Section: Introductionmentioning
confidence: 97%
“…Inside the same set of former topics, the fourth paper, "Reliability Monitoring Based on Higher-Order Statistics: A Scalable Proposal for the Smart Grid" [4] by O. Florencias et al, proposed a new index for both PQ and reliability assessment (depending on the considered analysis window's length) thought to be used in measurement campaigns that require deep statistical characterization. The index consists of a summation of three differential terms: variance, skewness, and kurtosis, each with respect to the ideal value of the statistic.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…Furthermore, other research has been focused on how to identify the different type of disturbances from occurring events; for instance, in References [6][7][8][9][10][11]. Once PQ disturbances are detected, classifying them and compressing them into separate events is a challenging task and requires advanced tools; see References [12][13][14][15]. Some authors have considered fuzzy logic or neural networks to classify them [16][17][18][19], some others proceed based on clustering the data depending on its origin from offline and prescribed events [20,21], and lastly, certain studies have focused on real-time classification, which results in a successful classification; for instance, see References [22][23][24].…”
Section: Introductionmentioning
confidence: 99%